Territoires du productivisme, paysages altérés - Alessandra Marcon (Projets de Paysage)
This article offers an analysis of the territories and landscapes altered by agro-industrial approaches fostered by productive goals. Given that these alterations are complex in nature and interwoven within different scales, urban planning and landscape architecture need new tools and critical approaches to help us understand and reinterpret the complexity of these alterations. The aim is to understand which tools can be used and how they can be combined to explore these landscapes and represent their complexity. The transect is thus seen as a possible exploratory and analytical experimental approach which is at the crossroads of urban planning and landscape architecture. The contribution is the fruit of doctoral research and is organised around the account of a transect journey made in the region of Vendée, a hybrid urban-rural territory and the birthplace of an ancient local production system specialised in the agri-food sector. Based on a first-hand account, the article proposes a journey organised along four sub-transects from the heart of the Bocage to the Atlantic coast of La Faute-sur-mer. The transect combines sensitive experiences, scientific investigation, the collection of testimonials and cartographic research. It brings to the surface the latent tensions and conflicts linked to the alterations affecting the landscape and its inhabitants. The transect is therefore a relevant tool both for revealing and understanding the complexity of altered landscapes and for thinking about alteration as a lever for creating a new approach to territory and landscape.